Relationship between sources and teachers’ sense of efficacy among novice teachers in Selangor, Malaysia - Saw, Hooi Chin; Roslan, Samsilah; Abdul Kadir, Suhaida; Mahyuddin, Rahil (Universiti Putra Malaysia Press, 2013)
This study investigated novice teachers’ sources of efficacy in relation to the application of knowledge in Educational Psychology. The questionnaires were administered to a sample of 160 novice teachers from 102 secondary schools in Selangor, Malaysia. The findings indicated that the novice teachers demonstrated a moderate level of teachers’ sense of efficacy. The three sources of efficacy, namely, mastery experience, vicarious experience, and social persuasion were identified as the predictors of teachers’ sense of efficacy [Adjusted R2 = 0.50, F (3, 155) = 53.16, p<0.01]. The implication of the study on the theory and practice of the teachers’ sense of efficacy was also discussed. Suggestions and recommendations were offered to enhance and foster senses’ of efficacy among the novice teachers.